Accurate and reproducible aortic growth rate mapping via registration of serial contrast-enhanced computed tomography angiograms. (14th October 2021) - Dux-Santoy, L; Rodriguez Palomares, J F; Teixido-Tura, G; Ruiz-Munoz, A; Casas, G; Valente, F; Servato, M L; Galian-Gay, L; Gutierrez, L; Gonzalez-Alujas, T; Fernandez-Galera, R; Evangelista, A; et al.
Abstract: Introduction: Accurate assessment of aortic diameters and growth rates is key for clinical management of patients with aortic aneurysms [1]. Manual assessment on multiplanar reformatted views of computed tomography angiograms (CTA) is recommended [1], although its reproducibility in the assessment of growth rates has not been reported [2]. Image registration has been proposed to provide 3D maps of aortic diameters and growth [3], but its accuracy and reproducibility have not been established. Purpose: To quantify accuracy and inter-observer reproducibility of aortic root and thoracic aorta diameters and growth rate by registration of serial CTAs compared to current standard. Methods: Forty non-operated patients with ≥2 contrast-enhanced ECG-gated CTA acquired at least 6 months apart were included. Aortic diameters and growth rates were measured in the aortic root and thoracic aorta by two independent observers, both with the current standard and with the registration-based technique. To perform registration-based assessment, each observer semi-automatically segmented the aorta at baseline and located typical anatomical landmarks (Fig. 1A). Then, deformable image registration was used to map baseline and follow-up CT scans and deformation was applied to the baseline aortic surface points to obtain their location at follow-up (Fig. 1B). Finally, aortic root diameters and growth rate and 3D maps of thoracic aortic diameters and growth rate were automatically obtained (Fig. 1C). Agreement between techniques and their inter-observer reproducibility were calculated. Results: Follow-up duration was 3.3±1.5 years (range 0.52–6.2). Compared with manual assessment, registration-based aortic diameters presented low bias and excellent agreement in the aortic root (0.42 mm, ICC=0.99) and the thoracic aorta (0.55 mm, ICC=0.99), and similar inter-observer reproducibility (ICC=0.99 for both). Compared with manual assessment, registration-based growth rates presented low bias and good agreement in the aortic root (0.12 mm/y, ICC=0.84) and the thoracic aorta (0.03 mm/y, ICC=0.77) (Fig. 2A), and much higher inter-observer reproducibility (ICC=0.96 vs 0.68 in the aortic root, ICC=0.96 vs 0.80 in the thoracic aorta) (Fig. 2B and C). Registration-based aortic growth rates reproducibility at 6 months follow-up was comparable to that obtained by manual assessment at 2.7 years (LoA = [−0.01, 0.33] and LoA = [−0.13, 0.21], respectively). Aortic diameters and growth rate 3D maps were highly reproducible (ICC>0.9) in the whole thoracic aorta. Conclusions: Progressive aortic dilation assessment via registration of CTAs is accurate and more reproducible than the current standard even over follow-ups as short as 6 months, and further provides robust 3D mapping of aortic diameters and growth rates. Its application may provide new insights in aneurysms pathophysiology and improve the clinical management of these patients. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This study has received funding from the Instituto de Salud Carlos III (PI17/00381). Guala A. has received funding from Spanish Ministry of Science, Innovation and Universities (IJC2018-037349-I).